2016
DOI: 10.1038/srep25573
|View full text |Cite
|
Sign up to set email alerts
|

Measuring changes in substrate utilization in the myocardium in response to fasting using hyperpolarized [1-13C]butyrate and [1-13C]pyruvate

Abstract: Cardiac dysfunction is often associated with a shift in substrate preference for ATP production. Hyperpolarized (HP) 13C magnetic resonance spectroscopy (MRS) has the unique ability to detect real-time metabolic changes in vivo due to its high sensitivity and specificity. Here a protocol using HP [1-13C]pyruvate and [1-13C]butyrate is used to measure carbohydrate versus fatty acid metabolism in vivo. Metabolic changes in fed and fasted Sprague Dawley rats (n = 36) were studied at 9.4 T after tail vein injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 55 publications
1
62
1
Order By: Relevance
“…The SNR and polarization level obtained in these experiments were sufficient to detect the downstream metabolites acetylcarnitine, bicarbonate and lactate, but a higher SNR would be required for detecting other metabolites and would be beneficial for imaging applications. The liquid‐state 13 C polarization obtained in the present study was considerably lower (∼3.3%) than the maximum achieved previously using TEMPO (∼13%) . Because nitroxyl radicals show a broader ESR spectrum if compared with the one arising from UV‐irradiated pyruvic acid, the lower DNP enhancement must result from the nonoptimal concentration of paramagnetic centers for the temperature and magnetic field strength.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The SNR and polarization level obtained in these experiments were sufficient to detect the downstream metabolites acetylcarnitine, bicarbonate and lactate, but a higher SNR would be required for detecting other metabolites and would be beneficial for imaging applications. The liquid‐state 13 C polarization obtained in the present study was considerably lower (∼3.3%) than the maximum achieved previously using TEMPO (∼13%) . Because nitroxyl radicals show a broader ESR spectrum if compared with the one arising from UV‐irradiated pyruvic acid, the lower DNP enhancement must result from the nonoptimal concentration of paramagnetic centers for the temperature and magnetic field strength.…”
Section: Discussioncontrasting
confidence: 66%
“…One of the consequences of the larger 13 C polarization obtained in our study with the persistent radicals was that the 13 C labeling of glutamate and acetoacetate could be observed, but there was no attempt to filter or scavenge the nitroxyl radicals, which were injected together with the substrates. Because of the spectral overlap with metabolites originating from pyruvate metabolism, the resonances of β‐hydroxybutyrate and citrate, which have been observed in previous studies using hyperpolarized butyrate and persistent radicals, could not be observed . However, the wide versatility of photo‐induced nonpersistent radicals permits the hyperpolarization of substrate mixtures containing unlabeled pyruvic acid.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this work, we have investigated the use of hyperpolarized 13 C‐labelled acetoacetate and β‐hydroxybutyrate as novel probes in the study of cardiac metabolism. Although several studies have shown the appearance of ketone bodies following the injection of related probes, such as [1‐ 13 C]butyrate and [2‐ 13 C]pyruvic acid, the in vivo rate of appearance of ketone bodies is necessarily limited owing to organ specificity and the number of separate biochemical reactions required to produce them. The interpretation of the visible appearance (or lack thereof) of ketone bodies produced following the injection of these other probes is not necessarily straightforward and, in particular, the absence of evidence of a particular ketone body is not sufficient evidence of its absence.…”
Section: Introductionmentioning
confidence: 99%
“…Isoflurane is the most commonly used anesthetic nowadays . In a typical setting, the depth of anesthesia is adjusted on the basis of the heart rate (HR) and rate of breathing . Thus, the actual amount of narcotic agent consumed by the animal remains difficult to assess.…”
Section: Introductionmentioning
confidence: 99%